2011
DOI: 10.1051/0004-6361/201116742
|View full text |Cite
|
Sign up to set email alerts
|

A large Hαline forming region for the massive interacting binaries β Lyrae and υ Sagitarii

Abstract: Aims. This study aims at constraining the properties of two interacting binary systems by measuring their continuum-forming region in the visible and the forming regions of some emission lines, in particular Hα, using optical interferometry. Methods. We have obtained visible medium (R ∼ 1000) spectral resolution interferometric observations of β Lyr and of υ Sgr using the VEGA instrument of the CHARA array. For both systems, visible continuum (520/640 nm) visibilities were estimated and differential interferom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
5
34
0
Order By: Relevance
“…We note that during 2009, when the redshifted portions of the rotating disk were beginning to occult the blueshifted side of the F star, three of four profiles show V <1 for λ < λ o , with λ o the central wavelength of the line, suggesting that photons from the F star are being scattered by extended hydrogen associated with disk material -which mainly covers the blueshifted hemisphere of the F star during ingress (2009). Phase shifts in three of the four spectra are positive, implying a source offset (Bonneau et al 2011a;Meilland et al 2011) to the south of the F star photocentre, which is consistent with the disk's orbital plane offset as defined by the interferometric imaging. The visibility in the Si II line shows some differential signal with respect to the continuum during 2009, but the amplitudes are minimal, with a small amount of blueshift relative to the line core.…”
Section: Qualitative Behavior Of the Differential Visibilitiessupporting
confidence: 68%
See 1 more Smart Citation
“…We note that during 2009, when the redshifted portions of the rotating disk were beginning to occult the blueshifted side of the F star, three of four profiles show V <1 for λ < λ o , with λ o the central wavelength of the line, suggesting that photons from the F star are being scattered by extended hydrogen associated with disk material -which mainly covers the blueshifted hemisphere of the F star during ingress (2009). Phase shifts in three of the four spectra are positive, implying a source offset (Bonneau et al 2011a;Meilland et al 2011) to the south of the F star photocentre, which is consistent with the disk's orbital plane offset as defined by the interferometric imaging. The visibility in the Si II line shows some differential signal with respect to the continuum during 2009, but the amplitudes are minimal, with a small amount of blueshift relative to the line core.…”
Section: Qualitative Behavior Of the Differential Visibilitiessupporting
confidence: 68%
“…This gaussian function is used to extract the minimum value of the visibility and the associated radial velocity and to estimate the full width at half maximum (in radial velocity) of the visibility drop. All the differential phase measurements have been oriented in the same way, which means that a positive offset represents an astrometric displacement towards the south in our case (Bonneau et al 2011a;Meilland et al 2011). The uncertainties of the differential interferometric quantities are obtained from a pure photon noise analysis.…”
Section: Obtaining the Differential Quantitiesmentioning
confidence: 99%
“…The B5-A0 supergiant status (rather than F2p, given in SIM-BAD) indicates M sp to be about 10 and makes the Malkov et al (2012) M sp estimations (1.35) incorrect. As the hotter, unseen secondary component seems to be more massive (Bonneau et al 2011), the minimum total mass of the system should be at least ≈ 20 which is more consistent with the Malkov et al (2012), M ph =32.1. Yet, Bonneau et al (2011) mention that the separation of the stars may have been much smaller than estimated.…”
Section: Wds 00174+0853 (=Hip 1392)mentioning
confidence: 65%
“…This massive, single-lined spectroscopic binary contains a bright star and an unseen companion. In their medium spectral resolution interferometric observations, Bonneau et al (2011) found WDS 19217−1557 (= υ Sgr) to be an interactive binary with a non-conservative evolution. The B5-A0 supergiant status (rather than F2p, given in SIM-BAD) indicates M sp to be about 10 and makes the Malkov et al (2012) M sp estimations (1.35) incorrect.…”
Section: Wds 00174+0853 (=Hip 1392)mentioning
confidence: 99%
“…On these images two components are seen, one unresolved, the primary, and one elongated, the secondary surrounded by the accretion disk. To go further in this study, and disentangle the stellar and circumstellar emission, the system was also observed in Hα with the CHARA/VEGA instrument (Bonneau et al 2011). The authors found that the emission was coming from a structure larger than the binary separation, most probably a circumbinary disk with possible contributions from polar jets.…”
Section: The Multiplicity Of Massive Starsmentioning
confidence: 98%